Automatic Greenhouse Monitoring System - Shazeb, Mohammed Safeeruddin; Santosh, Doijode; Bedi, Harpreet (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to design an automated system for a greenhouse and to monitor, control the system from a device through wired or remote access. This project addresses some of the issues in traditional farming. Issues like incapability of agriculture due to small and fragmented land holdings, risk in using manures and pesticides, lack of mechanization. The main part of the project is the module which will be referred to as AGMS (Automatic Greenhouse Monitoring System) and it consists of all the electronics and sensors needed for the work. There are also two more segments, one being the cloud and the other, the monitoring of data and control of the module which will be at the end user. It also discusses the various technical aspects of the module mainly focusing on the cloud and the end user also referring to the flexibility of the module itself.